Decision Support System for Priority Improvement of School Rooms at SD Negeri 020254 Binjai City to Obtain Special Allocation Fund (DAK) Assistance Using the MOORA Method - Dhany Fachrizal; Marto Sihombing; Siswan Syahputra (International Journal of Health Engineering and Technology, 2022)
The school room in the school building has an important function for the development and growth of education at SD Negeri 020254 Binjai City in realizing quality improvement and human resource development. The government through the Ministry of Education and Culture (Kemendikbud) provides a Special Allocation Fund (DAK). The DAK assistance provided by the Government aims to ensure that schools can improve school facilities and infrastructure for teaching and learning activities in schools to run optimally. The problem faced by the elementary school is to choose and determine the space in the school building that is prioritized for repair because it is not possible to renovate the school as a whole. The Moora Method Decision Support System (SPK) can help elementary schools in helping to solve these problems. From the results of the calculations carried out, the results with the highest score were obtained, namely the student bathroom room with a value of 0.3181. Thus the student's bathroom space is prioritized for repairs.